2015
DOI: 10.1371/journal.pone.0131576
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Plasmodium falciparum Histidine-Rich Protein 2 (pfhrp2) and Histidine-Rich Protein 3 (pfhrp3) Genes in Colombian Parasites

Abstract: A number of studies have analyzed the performance of malaria rapid diagnostic tests (RDTs) in Colombia with discrepancies in performance being attributed to a combination of factors such as parasite levels, interpretation of RDT results and/or the handling and storage of RDT kits. However, some of the inconsistencies observed with results from Plasmodium falciparum histidine-rich protein 2 (PfHRP2)-based RDTs could also be explained by the deletion of the gene that encodes the protein, pfhrp2, and its structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 40 publications
10
66
0
Order By: Relevance
“…However, this approach may be compromised by the emergence of P. falciparum parasites with deleted pfhrp2. South America was the first region to report the occurrence of false negative RDT results due to this gene deletion (Gamboa et al, 2010;Akinyi et al, 2013;Abdallah et al, 2015;Akinyi Okoth et al, 2015;Murillo Solano et al, 2015;Rachid Viana et al, 2017). Similar evidence was followed by more recent studies from Africa (Dolo et al, 2012;Wurtz et al, 2013;Parr et al, 2016;Beshir et al, 2017) and Asia (Kumar et al, 2013;Li et al, 2015;Bharti et al, 2016).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, this approach may be compromised by the emergence of P. falciparum parasites with deleted pfhrp2. South America was the first region to report the occurrence of false negative RDT results due to this gene deletion (Gamboa et al, 2010;Akinyi et al, 2013;Abdallah et al, 2015;Akinyi Okoth et al, 2015;Murillo Solano et al, 2015;Rachid Viana et al, 2017). Similar evidence was followed by more recent studies from Africa (Dolo et al, 2012;Wurtz et al, 2013;Parr et al, 2016;Beshir et al, 2017) and Asia (Kumar et al, 2013;Li et al, 2015;Bharti et al, 2016).…”
Section: Introductionmentioning
confidence: 64%
“…Meta-analysis was then performed on the remaining ten studies. These studies consisted of data from Bolivia (Rachid Viana et al, 2017), Brazil (Rachid Viana et al, 2017), Colombia (Murillo Solano et al, 2015;Dorado et al, 2016), French Guiana (Trouvay et al, 2013), Guyana , Honduras (Abdallah et al, 2015), Peru (Gamboa et al, 2010), and Suriname (Akinyi Okoth et al, 2015) in South America, and from Eritrea (Menegon et al, 2017;Berhane et al, 2018), Ghana (Amoah et al, 2016), and Kenya (Beshir et al, 2017) in Africa .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the associated risk of overtreatment of uninfected cases is considered more acceptable in malaria endemic zones than taking the risk of failing to detect cases. Recently, there has been reports of deletion of HRP2 gene which may lead to false RDT negative results [47, 48]. However, studies conducted in Africa showed HRP2 deletion in very small numbers of parasite isolates [49, 50], hence highly unlikely that the phenomenon may have influenced the results of this survey.…”
Section: Discussionmentioning
confidence: 95%
“…The targeted antigens are abundant in the sexual and asexual stages of the parasites, while histidine-rich protein 2 (Pf-HRP2) based RDT is specific for P. falciparum and lactate dehydrogenase (Pf-LDH & Pv-LDH) specific for detecting both P. falciparum and P. vivax . Pan based RDT targets specific antigens including lactate dehydrogenase (P-LDH) and aldolase proteins found in all Plasmodium species (Akinyi Okoth et al, 2015; Murillo Solano et al, 2015). Several factors potentially affect the accuracy and false-negative results of RDT including the interpretation of the test strip colour change, the density of malaria infection in the host, improper storage/handling of the kit and poor test performance (Echeverry et al, 2016).…”
Section: Discussionmentioning
confidence: 99%